2016
DOI: 10.1002/2016je005025
|View full text |Cite
|
Sign up to set email alerts
|

The collapse of Io's primary atmosphere in Jupiter eclipse

Abstract: Volcanic outgassing due to tidal heating is the ultimate source of a tenuous SO2 atmosphere around Jupiter's moon Io. The question of whether SO2 frost on the surface plays a part, and to what degree, in maintaining Io's atmosphere with the constant volcanic outgassing is still debated. It is believed that for a sublimation‐supported atmosphere, the primary atmosphere should collapse during eclipses by Jupiter, as the SO2 vapor pressure is strongly coupled to the temperature of the ice on the surface. No direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
3
34
1
Order By: Relevance
“…Tsang et al () did not detect post eclipse change in absorption by SO 2 at near‐ultraviolet (NUV) wavelengths. Yet infrared (IR) observations of Io going into eclipse by Tsang et al () revealed changes in the SO 2 absorption, consistent with a drop of the SO 2 column density by a factor of 5.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Tsang et al () did not detect post eclipse change in absorption by SO 2 at near‐ultraviolet (NUV) wavelengths. Yet infrared (IR) observations of Io going into eclipse by Tsang et al () revealed changes in the SO 2 absorption, consistent with a drop of the SO 2 column density by a factor of 5.…”
Section: Introductionmentioning
confidence: 76%
“…Io's SO 2 dominated atmosphere is tenuous and highly spatially variable. Previous ground‐based observation of the Io's atmosphere showed that its surface temperature drops and atmospheric column density collapses within ∼20 min past eclipse (see Figure of Tsang et al, ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Under this scenario, the required bulk atmospheric gas density and surface pressure are n ∼ 10 11 cm −3 and 1-3 nbar, consistent with observations and modeling of Io's dayside atmosphere at altitudes below 10 km (Lellouch et al 2007; Walker et al 2010). These densities and pressures would be too high for the nightside density if the atmospheric density drops by an order of magnitude or more at night (as predicted by sublimation-supported models), but recent results have shown a drop in SO 2 gas density of only a factor of 5±2 (Tsang et al 2016). While our observations taken immediately post-ingress and pre-egress (on different dates) prefer models with only a factor of 1.5 change in gas density, a factor of 5 change is still well within uncertainties.…”
mentioning
confidence: 99%
“…While our observations taken immediately post-ingress and pre-egress (on different dates) prefer models with only a factor of 1.5 change in gas density, a factor of 5 change is still well within uncertainties. In addition, our derived gas densities are for the total bulk atmosphere, while Tsang et al (2016) specifically measured SO 2 . The low-temperature gas component is warmer for observations in the first 20 minutes of eclipse (in Dec 2015) than after Io had been in shadow for 1.5 hours (in May 2016), suggesting cooling of the atmosphere during eclipse.…”
mentioning
confidence: 99%